Characterizing and Improving Spatial Visualization Skills - Titus, Sarah; Horsman, Eric (Journal of geoscience education, 2009)
Three-dimensional spatial visualization is an essential skill for geoscientists. We conducted two evaluations of students' spatial skills to examine whether their skills improve after enrollment in a geology course or courses. First, we present results of pre- and post-course survey of abstract visualization skills used to characterize the range of spatial abilities in the student population at Carleton College. In Introductory Geology, there was a correlation between those who score very poorly on the spatial survey and those who receive a grade of C or lower. Students in higher-level courses had better developed visualization skills than those in Introductory Geology. Gender differences disappeared in upper-level courses except for the spatial relations (mental rotation) task, where male students consistently outperformed females. Second, we describe the efficacy of instructional materials designed for a Structural Geology course at the University of Wisconsin. This study included a qualitative controlled experiment investigating whether frequent use of stereographic projections affected student performance on exam questions requiring spatial skills. The results of both the survey-based quantitative study and materials-based qualitative study suggest that students' spatial abilities can improve through practice provided in geology courses.